18S rDNA phylogeny of Clitellata (Annelida) - Erseus, Christer; Kallersjo, Mari (Zoologica Scripta, 2004)
The phylogeny of Clitellata was analysed using 18S rDNA sequences of a selection of species representing Hirudinida, Acanthobdellida, Branchiobdellida and 10 oligochaetous families. Eleven new 18S sequences of Capilloventridae (one), Haplotaxidae (one), Propappidae (one), Enchytraeidae (two), Lumbricidae (one), Almidae (one), Megascolecidae (two), Lumbriculidae (one), and Phreodrilidae (one) are reported and aligned together with corresponding sequences of 28 previously studied clitellate taxa. Twelve polychaete species were used as an outgroup. The analysis supports an earlier hypothesis based on morphological features that Capilloventridae represents a basal clade of Clitellata; in the 18S tree it shows a sister-group relationship to all other clitellates. The remaining clitellate taxa form a basal dichotomy, one clade containing Tubificidae (including the former 'Naididae'), Phreodrilidae, Haplotaxidae, and Propappidae, the other clade with two subgroups: (1) Lumbriculidae together with all leech-like taxa (Acanthobdellida, Branchiobdellida and Hirudinida), and (2) Enchytraeidae together with a monophyletic group of all earthworms included in the study (Lumbricidae, Almidae and Megascolecidae). These earthworms are members of the taxon Crassiclitellata, the monophyly of which is thus supported by the data. The tree also shows support for the hypothesis that the first clitellates were aquatic. The position of the single species representing Haplotaxidae is not as basal as could have been expected from earlier morphology-based conclusions about the ancestral status of this family. However, if Haplotaxidae is indeed a paraphyletic assemblage of relict taxa, a higher number of representatives will be needed to resolve its exact relationships with the other clitellates.